Statesman - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Statesman" by Plato is a Socratic dialogue that follows the action of the "Sophist." The work depicts a philosophical conversation seeking to define what makes a true statesman, distinguishing this figure from both sophist and philosopher. Through dialectical investigation and the method of division, the interlocutors explore whether genuine political power requires specialized knowledge of just rule$1 (Bor whether most rulers merely imitate such wisdom without possessing it. The dialogue raises questions about who should govern and why. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Statesman_(dialogue)
Release date is 1999-05-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Political science -- Early works to 1800